KONTROL STRUKTUR GEOLOGI TERHADAP JEBAKAN TEMBAGA SEBAGAI ARAHAN EKSPLOITASI DI DAERAH NGERJO DAN SEKITARNYA KECAMATAN TIRTOMOYO KABUPATEN WONOGIRI PROPINSI JAWA TENGAH = STRUCTURAL GEOLOGICAL CONTROL OF COPPER ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
The aim of this research is to know the pattern and the type of faults controlling the distribution of copper deposit and to define the direction for the exploitation. The research area is Ngerjo and its vicinity, Tirtomoyo District, Wonogiri Regency, Central Java, which is topographic map scale 1 : 25.000 sheet no. 49/XLII-q. The research begins with secondary data examination, interpretation of landsat image scale 1 : 125.000, interpretation topographic map scale 1 : 25.000 and interpretation of air photograph scale 1 : 10.000. These steps are then followed by field investigation (surface geological mapping) and laboratory analyses. The data are then integrated and presented especially on geological, structural and copper deposit distribution maps. Rivers and hills in the research area exhibit certain lineament patterns, trending northwest - southeast and northeast - southwest. These landscape patterns are interpreted to be controlled by geological structures. The lithologies in the research area are grouped into 5 informal lithostratigraphic units and one deposit, from the oldest to the youngest, as follow: Panggang breccia, Semilir breccia, Nglanggran breccia, Tenggar-Ngelo andesite, Dondong dacite units and sand-gravel deposit. These rock units are the products of Tertiary (Oligocene - Miocene) volcano. The geological structure controlling the research area consists of joints, syncline and lateral faults. The copper bearing quartz veins are associated with the northwest - southeast trending sinistral faults (Ngerjo and Sekandangan faults), northeast - southwest trending dextral faults (Ngelo fault) and north - south trending sinistral faults (Dawuhan fault). The veins are generally distributed near the large (minimum diameter 1 km) and hydrothermally altered intrusion body.These facts lead to a conclusion that the copper deposit distribution is controlled by the faults trending northwest - southeast, northeast - southwest and north - south, as well as the size of hydrothermally altered intrusion body. Key words : copper, fault, hydrothermal and intrusion